Everyday Life in the Balkans - Montgomery, David W., 1968- (Book collections on Project MUSE., 2019)
Everyday Life in the Balkansgathers the work of leading scholars across disciplines to provide a broad overview of the countries of Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Kosovo, Macedonia, Romania, Serbia, and Turkey. This region has long been characterized as a place of instability and political turmoil, from World War I, through the Yugoslav Wars, and even today as debate continues over issues such as the influx of refugees or the expansion of the European Union. However, the work gathered here moves beyond the images of war and post-socialist stagnation which dominate Western media coverage of the region to instead focus on the lived experiences of the people in these countries. Contributors consider a wide range of issues including family dynamics, gay rights, war memory, religion, cinema, fashion, and politics. Using clear language and engaging examples,Everyday Life in the Balkansprovides the background context necessary for an enlightened conversation about the policies, economics, and culture of the region.